2018
DOI: 10.3389/fphys.2018.00253
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue as a Relevant Fat Depot for Cardiovascular Risk in Obesity

Abstract: Obesity is associated with increased risk of premature death, morbidity, and mortality from several cardiovascular diseases (CVDs), including stroke, coronary heart disease (CHD), myocardial infarction, and congestive heart failure. However, this is not a straightforward relationship. Although several studies have substantiated that obesity confers an independent and additive risk of all-cause and cardiovascular death, there is significant variability in these associations, with some lean individuals developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 175 publications
1
47
0
5
Order By: Relevance
“…Perivascular adipose tissue (PVAT) is adipose tissue that surrounds large arteries and releases various factors, in paracrine or autocrine fashion, in the regulation of vascular function. PVAT has the ability to release proinflammatory adipokines or cytokines after insult and, consequently, promote inflammation, vasoconstriction, and VSMCs proliferation, which are all highly associated with cardiovascular risk, especially in obesity (Figure 2, yellow) [82]. Numerous studies have shown that PVAT plays a protective role against atherosclerosis by increasing the adiponectin level and eNOS expression, thereby inhibiting plaque formation, reducing inflammation, and improving endothelial function [83].…”
Section: Sirt1 Restore Perivascular Adipose Tissue Dysregulationmentioning
confidence: 99%
“…Perivascular adipose tissue (PVAT) is adipose tissue that surrounds large arteries and releases various factors, in paracrine or autocrine fashion, in the regulation of vascular function. PVAT has the ability to release proinflammatory adipokines or cytokines after insult and, consequently, promote inflammation, vasoconstriction, and VSMCs proliferation, which are all highly associated with cardiovascular risk, especially in obesity (Figure 2, yellow) [82]. Numerous studies have shown that PVAT plays a protective role against atherosclerosis by increasing the adiponectin level and eNOS expression, thereby inhibiting plaque formation, reducing inflammation, and improving endothelial function [83].…”
Section: Sirt1 Restore Perivascular Adipose Tissue Dysregulationmentioning
confidence: 99%
“…Although it has been previously considered an inert component of the vascular wall, displaying a structural role, PVAT is currently seen as a key role tissue in vascular homeostasis and in the maintenance of the arterial tension (2).…”
Section: Pvat and Hypertensionmentioning
confidence: 99%
“…The white adipose tissue (WAT), composed predominantly of cells exhibiting unilocular lipid inclusions, is mainly located in the hypodermis and perivisceral location. The brown adipose tissue (BAT), temporarily occurring in humans in the interscapular and mediastinal regions, is involved in the maintenance of a consistent body temperature, containing adipocytes with multiple cytoplasmic inclusions, of variable size, associated with a rich capillary network (1,2). The beige or brite (brown-in-white) adipose tissue (BeAT) may be disposed in between WAT cells and is able to develop a brown-like phenotype (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations